A identidade do herói vegano : uma análise entre as relações das dimensões de identidade e os tipos de arquétipo dos consumidores veganos - Santos, Monica Negri dos (2021)
Vegans are those who do not consume any animal products. Since this group is growing in Brazil (IBOPE, 2020), this study seeks to propose a framework that relates the dimensions of identity and the types of archetypes of these consumers, as archetypes are seen as identity profiles. To achieve this purpose, this exploratory study was based on the theoretical framework of identity and its dimensions (contextual, internal and external), archetypes and existing studies on vegan consumer behavior. It was possible to verify the identity in its three dimensions, a framework was created with the similarities of the stories of the beginning of vegetarianism and veganism, it was possible to identify that society is open to differences in this type of consumption. In addition, the work also contributes with data on the relationships of vegans with omnivores, since most respondents reported that they would not have romantic relationships with people who were not vegetarians or vegans, and on vegan consumption, it was identified in this research that there are two types of vegans: the orthodox, who consume only organic products or strictly vegan companies, and the tolerant, who consume vegan products, even if the industry that produced this product has other products of animal origin. Finally, it was possible to characterize that the Sage, Outlaw, Normal Guy and Governor archetypes are presented in certain phases, although the Hero archetype was presented in all interviewees' narratives, data that can help organizations in the format of characters for advertising.